Next-Generation in vivo Modeling of Human Cancers - Gargiulo, Gaetano (Frontiers in Oncology, 2018)
Animal models of human cancers have played a major role in our current understanding of the fundamental biology of tumors. In pre-clinical Oncology, animal models have been crucial assets in drug target and biomarker discovery and validation. In turn, this was translated in improved care for cancer patients. Technological breakthrough in genetic engineering and single cell ‘omics’ offers tremendous potential to improve the informative value of pre-clinical models in the quest for understanding and treat a diverse spectrum of cancer types. Here, I review the state-of-art in modeling human cancers with focus on animal models for human malignant gliomas. I build on this ground as a basis for a more general discussion of the potential ways in which transformative technologies may shape the next-generation of pre-clinical models. I argue that refining animal models along the proposed line will increase the success rate of translation for pre-clinical research in Oncology.